Measuring impacts on species with models and metrics of varying ecological and computational complexity. Issue 6 (3rd July 2020) - Hallam, Christopher D.; Wintle, Brendan A.; Kujala, Heini; Whitehead, Amy L.; Nicholson, Emily
Abstract: Approaches to assess the impacts of landscape disturbance scenarios on species range from metrics based on patterns of occurrence or habitat to comprehensive models that explicitly include ecological processes. The choice of metrics and models affects how impacts are interpreted and conservation decisions. We explored the impacts of 3 realistic disturbance scenarios on 4 species with different ecological and taxonomic traits. We used progressively more complex models and metrics to evaluate relative impact and rank of scenarios on the species. Models ranged from species distribution models that relied on implicit assumptions about environmental factors and species presence to highly parameterized spatially explicit population models that explicitly included ecological processes and stochasticity. Metrics performed consistently in ranking different scenarios in order of severity primarily when variation in impact was driven by habitat amount. However, they differed in rank for cases where dispersal dynamics were critical in influencing metapopulation persistence. Impacts of scenarios on species with low dispersal ability were better characterized using models that explicitly captured these processes. Metapopulation capacity provided rank orders that most consistently correlated with those from highly parameterized and data‐rich models and incorporated information about dispersal with little additional computational and data cost. Our results highlight the importance of explicitly considering species' ecology, spatial configuration of habitat, and disturbance when choosing indicators of species persistence. We suggest using hybrid approaches that are a mixture of simple and complex models to improve multispecies assessments. Abstract : Article impact statement : Not explicitly including ecological complexity in biodiversity metrics may result in misleading conclusions when assessing impacts. Abstract : Medición de los Impactos sobre las Especies con Modelos y Medidas de Complejidad Ecológica y Computacional Variante Resumen: Las estrategias para evaluar el impacto de los escenarios de perturbación de paisaje sobre la distribución de las especies van desde las medidas basadas en patrones de presencia o hábitat hasta los modelos integrales que incluyen explícitamente a los procesos ecológicos. La elección de medidas y modelos afecta la interpretación de los impactos y las decisiones de conservación. Exploramos los impactos de tres escenarios realistas de perturbación sobre cuatro especies con características ecológicas y taxonómicas diferentes. Usamos progresivamente modelos y medidas más complejas para evaluar el impacto relativo y la clasificación de los escenarios sobre las especies. Los modelos variaron desde aquellos de distribución de especies que dependen de las suposiciones implícitas acerca de los factores ambientales y la presencia de la especie hasta aquellos modelos poblacionales explícitos con una alta parametrización espacial que incluyen los procesos ecológicos y la estocasticidad. Las medidas tuvieron un desempeño uniforme en la clasificación de los diferentes escenarios de acuerdo a la gravedad, principalmente cuando la variación en el impacto fue causada por la cantidad de hábitat presente. Sin embargo, las medidas difirieron en la clasificación para los casos en los que las dinámicas de dispersión fueron significativas en la influencia de la persistencia metapoblacional. Los impactos de los escenarios sobre las especies con una habilidad reducida de dispersión estuvieron mejor caracterizados con el uso de modelos que capturaron explícitamente estos procesos. La capacidad metapoblacional proporcionó categorías de clasificación con la correlación más consistente a aquellas provenientes de los modelos ricos en datos y con una alta parametrización e incorporó información sobre la dispersión con un reducido costo adicional de cómputo y de datos. Nuestros resultados resaltan la importancia de la consideración explícita de la ecología de las especies, la configuración espacial del hábitat y la perturbación cuando se eligen los indicadores de la persistencia de una especie. Sugerimos que se usen estrategias híbridas que mezclen modelos simples y complejos para mejorar las evaluaciones realizadas a múltiples especies. 摘要: 评估景观干扰情景对物种影响的方法包括基于物种出现格局或栖息地格局的指标和纳入生态过程的综合模型等。对指标和模型的选择会影响对物种所受影响的解读和保护决策。本研究探索了三种真实干扰情景对四种不同生态学特征和类群的物种的影响。我们使用了逐渐复杂化的模型和指标评估了干扰情景对物种的相对影响和影响等级。本研究涉及的模型包括依赖于环境因素和物种出现的隐式假设的物种分布模型, 以及明确包含生态过程和随机性的高度参数化的空间显式种群模型。当影响的变化是由栖息地数量驱动时, 各种指标对不同情景的影响严重程度排序的结果一致。然而, 当扩散动态对集合种群续存有重要影响时, 不同指标的排序结果不同。使用明确考虑了扩散过程的模型可以更好地描述干扰情景对扩散能力弱的物种的影响。集合种群承载力提供了与高度参数化和数据丰富的模型最为一致的排序, 并且可以在几乎没有额外计算和数据成本的情况下加入扩散的信息。我们的结果强调了选择物种续存指标时应清楚地考虑物种的生态特征、栖息地空间结构以及干扰。我们建议使用简单和复杂模型混合的方法来改进多物种评估。【翻译: 胡怡思; 审校: 聂永刚】